Study of the Phenomenon of Homonymy (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Although homonyms have been studied by different scientists in different periods, the issue of how they are formed has not been given much importance, the effectiveness of homonyms in different parameters, lexicographic interpretation and principles have not been sufficiently studied. From a scientific-theoretical point of view, their specific aspects have not been sufficiently theoretically substantiated. This determines the need to research this topic. The article is devoted to the analysis of the process of semantic formation of homonyms in the Uzbek language. It is known that perception has its own role in the formation of homonyms. This article discusses the role of perception in the formation of homonyms.